(untitled) (Journal of Social Sciences Review, 2023)
The current study is about the discriminatory attitudes and behaviors with nurses in healthcare management as a manager equal to the doctor which is not yet recognized by the doctors. The study was carried out employing the qualitative research methods in order to understand the research problem through the perspectives of affected population. The researchers chose to conduct this study to investigate the problem through the nurses’ perspectives. The sampling type was purposive whereby the research participants who have lived experiences are selected for the in-depth interviews. The sample size of the study is 5 nurses (male) serving as in the government hospitals. The researcher collected the data in natural settings from the targeted population. The researchers used thematic analysis for research findings of the study. All collected data were transcribed and coded to develop the categories and themes. The findings of the study reveal that the nurses are discriminated by the doctor community who are health administrators in government hospitals. This attitudes and behavior is manifested on different fronts such as politically, socially and professionally. Such an attitude diminishes the creativity and enthusiasm of the nurse medical practitioners due to the injustice on professional grounds. Although, nurses claim that they can be health administrators if government authorized them and put them into these key administrative positions to serve even better.